PENENTUAN ANGKA KELUAR PERALATAN UNTUK EVALUASI KEANDALAN SISTEM DISTRIBUSI TENAGA LISTRIK - Hartati, Rukmi Sari (Majalah Ilmiah Teknologi Elektro, 2007)
The quality of electricity supply at consumerâ€™s side is highly affected by its distribution networks. The distribution system reliability can be determined by using a number of reliability indices. The most commonly used indices are SAIFI (Systems Average Interruption Frequency Index) and SAIDI (Systems Average Interruption Duration Index). The calculation of SAIFI and SAIDI requires probability of outage indices for installed power system equipment (Î»).Calculation of reliability indices usually follows PLN Standard SPLN 59:1985. Within the standard, the Î» value for distribution line is divided into 2 categories, which are overhead and underground distribution lines. In fact, there are a number of conductor types used for distribution lines that may have different values of Î». This research is focused to a determination of Î» values for AAACOC (All Aluminium Alloy Conductor Cable) and MVTIC (Medium Voltage Twisted Insulated Cable). Distribution system failure data is collected from a number of distribution lines in Bali. Data collection was carried out using a TMP (â€œTingkat Mutu Pelayananâ€/Service Quality Level) Recorder. Data analysis then carried out to calculate the Î» values and the reliability indices. The new Î» values for AAACOC and MVTIC are found to be 0.187 and 0.089/km/year, respectively. The results indicated that the new value of Î» for AAACOC and MVTIC are more realistic and suitable for reliability analysis particularly in Bali Distribution Systems.